Organization as Communication: A Luhmannian Perspective - Schoeneborn, Dennis (Management communication quarterly, 2011)
This article introduces Luhmann’s theory of social systems as a prominent example of communication as constitutive of organization (CCO) thinking and argues that Luhmann’s perspective contributes to current conceptual debates on how communication constitutes organization. The theory of social systems highlights that organizations are fundamentally grounded in paradox because they are built on communicative events that are contingent by nature. Consequently, organizations are driven by the continuous need to deparadoxify their inherent contingency. In that respect, Luhmann’s approach fruitfully combines a processual, communicative conceptualization of organization with the notion of boundary and self-referentiality. Notwithstanding the merits of Luhmann’s approach, its accessibility tends to be limited due to the hermetic terminology that it employs and the fact that it neglects the role of material agency in the communicative construction of organizations.